Role of organic solvent addition to ionic liquid electrolytes for lithium–sulphur batteries. Issue 3 (5th December 2014) - Xiong, Shizhao; Scheers, Johan; Aguilera, Luis; Lim, Du-Hyun; Xie, Kai; Jacobsson, Per; Matic, Aleksandar
Abstract : A mixed organic solvent/ionic liquid electrolyte combined the beneficial properties of both worlds, high capacity and high safety, through the local arrangement around the Li-ion. Abstract : We investigate the role of the addition of an organic solvent to an ionic liquid electrolyte for the performance of lithium–sulphur (Li–S) batteries. We find that with a mixed electrolyte, formed by adding 10 wt% 1, 3-dioxolane (DIOX) to an ionic liquid, the capacity of a Li–S cell is more than doubled, the rate capability and the cycling performance considerably improved, compared to a cell utilizing a neat ionic liquid electrolyte. The improved performance can be correlated with an enhanced ion transport, evidenced by an increased ionic conductivity and higher limiting current density, directly related to a decrease in viscosity and glass transition temperature of the mixed electrolytes. We show that this in turn is linked to a change in the local environment of the Li-ions where the organic solvent is incorporated in the coordination shell. In addition we show that the mixed electrolytes have a considerably higher thermal stability, in particular a dramatically increased flash point, and improved low temperature properties with respect to a conventional organic solvent based electrolyte currently used for Li–S batteries.